Efeitos de inibidores da enzima COX-2 sobre o desenvolvimento de crises convulsivas em camundongos - Fava, Fernanda Rossatto Temp (2018)
Cyclooxygenase-2 (COX-2) inhibitors reduce the synthesis of prostaglandins (PGs) and play an important role in inflammation. In the last decades, research has been focused on the use of COX-2 inhibitors and the inflammatory process in the central nervous system (CNS). However, there is controversy about the role of COX-2 in acute seizures. Some studies have shown that COX-2 inibition decreases seizures, while others have reported that it may facilitate seizure episodes. Considering the current discrepancy regarding the pro and anticonvulsant acute effect of COX-2 inhibitors and the lack of studies investigating the effect of their subchronic administration, the aim of this study was to investigate whether the acute or subchronic administration of COX- 2 inhibitors, nimesulide, celecoxib and etoricoxib alter seizures. Male swiss mice (25-30 grams) were treated acutely with vehicle (0.1% carboxymethylcellulose in 5% Tween 80, p.o.) nimesulide, celecoxib or etoricoxib (0.2, 2 or 20 mg/kg, p.o.) 60 minutes prior to the administration of the seizure agent pentylenetetrazol (50 mg/kg, i.p.). In subchronic administrations studies the animals received vehicle (0.1% carboxymethylcellulose in 5% Tween 80, p.o.) or nimesulide, celecoxib or etoricoxib (0.2, 2 or 20 mg/kg, p.o.) daily for 14 consecutive days. On the 15th day, mice were challenged with PTZ (50 mg/kg, i.p). After PTZ administration the animals were monitored for 20 minutes for the appearance of myoclonic and generalized tonic-clonic seizures. The number of seizure episodes, total time spent seizing, and Racine score were recorded. After the behavioral analysis, the animals were euthanized and the cerebral cortex and hippocampus were dissected and homogenized for the analysis of pro- and anti-inflammatory mediators [interleukin-1β (IL-1β), interleukin-6 (IL-6), interferon-γ (IFN-γ), tumor necrosis factor -alfa (TNF-α), and interleukin-10 (IL-10)], prostaglandins (PGE2, PGF2α, and PGD2), thromboxanes (TXB2), in picrogram per milligram of protein (pg/mg) and prostaglandin receptor (EP1, EP2 and EP3) immunoreactivity. Acute administration of nimesulide increased the latency to myoclonic, generalized tonic-clonic tonic-clonic seizures induced by PTZ and decreased the number of seizure episodes. However, celecoxib and etoricoxib acutely did not alter the parameters analyzed. PTZ increased cytokine levels in the cerebral cortex and hippocampus. While etoricoxib had no effect, celecoxib and nimesulide attenuated the PTZ-induced increase in proinflammatory cytokines in the cerebral cortex. Nimesulide was the only COX-2 inhibitor that attenuated PTZ-induced seizures, which coincided with an increase in IL-10 levels in the cerebral cortex and hippocampus. In addition, subchronic administration of celecoxib decreased the latency to PTZ-induced generalized tonic-clonic seizures and the PTZ-induced increase in proinflammatory cytokines, but did not alter the PTZ-induced increase in PGE2 or IL-10 levels. In addition, subchronic administration of nimesulide and etoricoxib increased the latency to generalized tonic-clonic convulsive seizures induced by PTZ, decreased the PTZ-induced increase of PGE2 and potentiated the PTZ-induced increase of IL-10. We suggest that the anticonvulsive effect of nimesulide and etoricoxib may be related to their ability to decrease PTZ-induced production of PGE2 and to increase PTZ-induced IL-10 production in mice.